On the representation and evolution of Australian English and New Zealand English - Anne Przewozny; Cécile Viollain (Anglophonia)
Australian English (AusE) and New Zealand English (NZE) are two originally “transported” Englishes in the Southern hemisphere. Although there is currently no doubt among the scientific community that they constitute two distinct dialects of English with their own lexical, morphosyntactic, phonological and phonetic features, their description and representation have long been frozen into a unique “Australasian” dialect, in spite of an enormous amount of endocentric linguistic descriptions emerging in the second half of the twentieth century. AusE and NZE being amongst the latest varieties to have emerged in the English-speaking world, they have only recently been extensively studied and considered as valid research objects by the scientific community. In this article we first consider some historical arguments that eventually led to a misleading descriptive hotchpotch of AusE and NZE. This situation scarcely left any room for the possibility of specific phonological and/or phonetic variation within each variety, let alone the description of AusE and NZE as two separate linguistic entities in Australasia. After reconsidering a few parallel historical facts, common critical denunciations and lay theories on the origins of the two Austral varieties, the article focuses on the representation of AusE and NZE in the literature on the phonology of English accents around the world. With a view to contribute to the definition of AusE and NZE as linguistic objects in motion and to promote a dynamic portrait of each variety, we then provide contemporary oral data from the PAC programme as well as comparative analyses in favour of two major arguments for distinctiveness between AusE and NZE: rhoticity in NZE as well as the short front vowel shift in both AusE and NZE.